STRESSES IN COMPOSITE PLATES WITH RIVETED BARS USED FOR AIRCRAFT CONSTRUCTION - Marta MAKSYMOVYCH; Maciej DUTKIEWICZ; Olesia MAKSYMOVYCH (Scientific Journal of Silesian University of Technology. Series Transport)
Reinforcement of plates with rod systems is widely used in engineering, especially in aircraft construction. For example, An-178 aircraft. Removable panels on the lower surface of the wing half, located between the rear spar and the flaps. The method of calculating stresses and deformations in composite plates reinforced with rods is developed in the work. It is assumed that the rod is elastic, attached with rivets. Rivets were considered as rigid inclusions to which unknown forces were applied. These forces were determined from the condition of compatibility of plate and rod deformations. The singular integral equations' method was used to determine stresses and strains in the plate. Integral equations were solved numerically and reduced to a system of algebraic equations. To obtain the forces and moments acting on the rivets, the equations of equilibrium of the rivets and the conditions that ensure the same displacements between the rivets in the plate and in the rods are added to these equations. Examples of calculating stresses near circular and elliptical rivets, magnitudes of forces acting on rivets depending on the rigidity of the rods are given. The reduction of the stress concentration near the elliptical hole, which is placed between two rods, was studied.